BAR Domains and BAR Domain Superfamily Proteins - Sharma, Mahak; Caplan, Steve (Elsevier, 2022)
The BIN-Amphiphysin-Rvs (BAR) domain is an evolutionarily conserved region found in over 750 proteins. BAR domain superfamily members dimerize to form a surface capable of membrane sensing and binding. Such membrane remodeling is essential for the organization and function of intracellular organelles, thus influencing important cellular events, including endocytic and membrane trafficking, cell cycle, division, and migration. In this article, we examine the different subfamilies of BAR domain proteins and discuss how they exert their influence to shape membranes. We also focus on the roles of key BAR domain proteins and their roles in mediating actin assembly and intracellular transport and signaling.
Only IISER Mohali authors are available in the record.
Keywords: BAR Domains; BAR Domain Superfamily Proteins